Comprehensive Analysis of Imipenemase (IMP)-Type Metallo-β-Lactamase: A Global Distribution Threatening Asia - Pisut Pongchaikul; Paninee Mongkolsuk (MDPI AG, 2022)
Antibiotic resistance, particularly beta-lactam resistance, is a major problem worldwide. Imipenemase or IMP-type metallo-β-lactamase (MBL) has become a more prominent enzyme, especially in Asia, since it was discovered in the 1990s in Japan. There are currently 88 variants of IMP-type enzymes. The most commonly identified variant of IMP-type enzymes is IMP−1 variant. IMP-type MBLs have been detected in more than ten species in Enterobacterales. Pseudomonas aeruginosa is the most frequent carrier of IMP-type enzymes worldwide. In Asia, IMP-type MBLs have been distributed in many countries. This work investigated a variety of currently available IMP-type MBLs at both a global level and a regional level. Out of 88 variants of IMP-type MBLs reported worldwide, only 32 variants were found to have susceptibility profiles. Most of the bacterial isolates carrying IMP-type MBLs were resistant to Carbapenems, especially Imipenem and Meropenem, followed by the 3rd-generation cephalosporins, and interestingly, monobactams. Our results comprehensively indicated the distribution of IMP-type MBLs in Asia and raised the awareness of the situation of antimicrobial resistance in the region.